Perancangan E-Learning Berbasis Internet pada Sekolah SMK Negeri 13 Jakarta - Idris Gautama So; Fajar Kurniawan (Bina Nusantara University, 2010)
Technology advances in education is very influential for educators to solve problems such as lack of adequate study time, and lack of auxiliary equipment to support learning. Therefore, it is required to know how far SMKN 13 Jakarta will need e-Learning and the extent of readiness of existing infrastructure on students to support the implementation of e-Learning. The research method is direct survey by distributing questionnaires to students and interviews with teachers. The method of analysis used by researchers is to use SWOT analysis,Porter, and the Cost and Benefit. The results showed that the school does require an e-Learning to improve its services to the community and the students have sufficient infrastructure to support the implementation of e-Learning.